La construcción sostenible en Latinoamérica - Flores Carbajal, Percy Abel (2021)
This article explains the current state and advances of sustainable construction in Latin America. In addition, it shows different ways to contribute to sustainability from an architectural perspective: from design criteria to research providing input to such topic. The objective of this research is to promote the importance of sustainable, dignified and efficient buildings for a society facing the challenges of climate change.